Treatment of POME via chitosan based flocculation : study the effect of dosage chitosan in removal oil from POME - Joannes Victor, Valentine @ Dol (2008)
The treatments of palm oil mill effluent (POME) have been a topic of research in Malaysia. These effluents needs to be properly treated before it released to watercourse and minimize the environmental hazard. This research is conducted to evaluate the treatment of palm oil mill effluent (POME) using chitosan based flocculation. Chitosan is a biological product which was believes it is useful in water treatment as adsorbent to remove oil from wastewater. A study was conducted in the laboratory to compare chitosan concentration in different volume of dosage. The sample were undergo flocculation process by using Jar Test where six beaker of sample was treated with varies volume dosage. The comparison was made by analyzing their oil removal efficiency, reduction of suspended solid, turbidity, BOD and COD and as well as pH adjustment. The result indicated that chitosan concentration at ratio of 1wt% chitosan in 1% was performed better in increasing of volume doses and 2%wt chitosan in 7% acetic acid was better at optimum dosage more than 12ml. In conclusion, it shows that chitosan was effective in removal oil from POME with more than 90% efficiency.-Author